The Effect of KalDiDASH (DASH Diet Calendar) Usage on Knowledge Level and Diet Adherence Among Hypertension Patients the Kalibagor Village Posbindu - Rizki Cahyani; Tina Muzaenah (Proceedings Series on Health & Medical Sciences, 2024)
Background:Hypertension is a condition where an individual's systolic blood pressure is 140 mmHg, or higher and diastolic blood pressure is 90 mmHg or higher, occurring in both men and women. One recommended approach to manage hypertension is the DASH (Dietary Approaches to Stop Hypertension) diet. However, in implementing the hypertension diet, patients often lack knowledge about permissible foods and tend to follow the diet only immediately after seeking medical attention, with adherence declining after the first week. Method: This study employed a quantitative method with a pre-experimental design using a one-group pretest-posttest approach. The sample consisted of 27 respondents suffering from hypertension at PosbinduKalibagor Village, selected through the total sampling technique and G*Power software. Data analysis utilized Paired Sample T-Test with a significance level of 0.05. Results:There was a significant difference in the average knowledge level before and after DASH diet health education using the KalDiDASH media, with t(26) = -7.772, p = 0.001. There was also a significant difference in the average diet adherence level before and after using KalDiDASH, with t(26) = -2.993, p = 0.006. There was an effect of using KalDiDASH (DASH Diet Calendar) on the knowledge level and diet adherence of hypertension patients at the Kalibagor Village Posbindu, with p-values of 0.001 and 0.006 (less than 0.05), respectively, and a large effect size. Conclusion:Using KalDiDASH affects hypertension patients' knowledge level and diet adherence at the Kalibagor Village Posbindu.